Mahram dalam Perjalanan Jauh Serta Menerapkan Prinsip Islam di Tengah Perubahan Zaman - Marsya Al Farin; Bias Tirta Bayu; Dini Sartika; Zaky Raihan Febrianto; Wismanto Wismanto (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study examines the concept of mahram in long distance travel and how Islamic principles can be applied in the face of ongoing societal changes. The background of this research arises from the growing phenomenon of long-distance travel, whether for work, education, or religious purposes, often involving the participation of women. On the other hand, advancements in technology and global mobility have also influenced views and practices related to mahram, particularly in the context of Islamic law. The objective of this study is to explore the understanding of mahram in the context of long-distance travel and analyze how Islamic principles can remain relevant and be applied despite the changing times. This research employs a qualitative approach through a literature review, which includes an analysis of religious texts, contemporary fatwas, and scholars' perspectives on long-distance travel and mahram. The findings indicate that, despite the dynamics of social life, the principle of mahram remains essential in safeguarding the honor and safety of individuals, especially women, during long-distance travel. However, a more flexible understanding of the application of mahram has emerged in the modern era, considering factors such as security, technology, and the existing social context. This discussion aims to provide insights into the balance between upholding Islamic teachings and addressing the challenges of travel in the face of modernity.